Rheological, adhesive, and chemical characterization of asphalt mastic modified with spent coffee grounds: A comparative study with limestone filler - Manita Thairueng; Suwaphit Chamwon; Multazam Hutabarat; Preeda Chaturabong (Results in Engineering, 2026)
• SCG reduces G* by 13–21% and lowers the iso-stiffness temperature by up to 5.79°C after long-term aging. • Limestone mastics exhibit 25–83% higher pull-off force than SCG mastics, yet SCG maintains >85% moisture retention on basalt. • SEM reveals hydrophobic organic films on SCG driving the cohesive-to-adhesive failure transition under moisture exposure. Spent coffee grounds (SCG) were evaluated as an organic filler in asphalt mastic at 10%, 15%, and 20% by volume, benchmarked against limestone (LM). The experimental program combined DSR temperature sweeps, pull-off adhesion tests on basalt, granite, and marble substrates, SARA fractionation, and SEM, performed under fresh, RTFOT-aged, and PAV-aged conditions. At 20 wt% replacement, SCG reduced the complex shear modulus G* from 3,637 to 2,885 kPa at 16°C (−21%) and lowered the iso-stiffness temperature from 31.22°C to 25.43°C after PAV aging (−5.79°C), while limestone at 20 wt% raised G* to 6,461 kPa (+78%). The rutting factor G*/sinδ decreased by 19–23% with SCG and increased by 71–80% with LM at 64°C, whereas the fatigue factor G*sinδ at 25°C dropped by 18–22% with SCG, indicating improved fatigue resistance potential. Limestone mastics exhibited 25–83% higher pull-off force than SCG (p < 0.05, all 18 comparisons, Benjamini–Hochberg-corrected), yet SCG mastics maintained moisture retention of 83–97% on basalt, comparable to LM (75–97%). Failure mode analysis showed all mastics cohesive under dry conditions, with SCG transitioning to adhesive failure under moisture exposure (notably at 15–20% SCG on marble and granite after PAV aging). SARA analysis confirmed aromatics rose from 60.6% to 65.7% and asphaltenes fell from 10.7% to 8.2% with increasing SCG, yielding an Instability Colloidal Index decrease from 0.187 to 0.154. These results establish SCG not as a direct limestone substitute but as a complementary modifier suited to fatigue-prone warm-climate binder courses and hybrid SCG–LM filler blends, offering environmental benefits through agricultural waste valorization.
Keywords: Asphalt Pavement Performance Evaluation; Geotechnical Engineering and Soil Stabilization; Polymer Nanocomposites and Properties